Design, chemical synthesis and biological evaluation of 3-spiromorpholinone/3-spirocarbamate androsterone derivatives as inhibitors of 17β-hydroxysteroid dehydrogenase type 3. Issue 17 (1st September 2015) - Djigoué, Guy Bertrand; Kenmogne, Lucie Carolle; Roy, Jenny; Maltais, René; Poirier, Donald
Graphical abstract: Abstract: 17β-Hydroxysteroid dehydrogenase type 3 (17β-HSD3) is a key enzyme involved in the biosynthesis of testosterone and dihydrotestosterone. These hormones are known to stimulate androgen-dependent prostate cancer. In order to generate effective inhibitors of androgen biosynthesis without androgenic effect, we synthesized a new family of 3-spiromorpholinone and 3-spirocarbamate androsterone derivatives bearing diversified hydrophobic groups. We also tested their inhibitory activity in a microsomal fraction of 17β-HSD3-containing rat testes, and their androgenic effect on androgen-sensitive LAPC-4 cells. From our first structure–activity relationship (SAR) study, we noted that compound7e inhibited 17β-HSD3 (77% at 0.1 μM) compared to our reference compound RM-532-105 (76% at 0.1 μM), but exhibited a residual androgenic effect. A library of7e analogue compounds was next synthesized in order to generate compounds with reduced androgenic activity. In this new SAR study, the sulfonamide compound7e21 and the carboxamide compound7e22 inhibited 17β-HSD3 (IC50  = 28 and 88 nM, respectively). These two compounds were not androgenic and not cytotoxic even at the highest concentration tested, but their inhibitory activity decreased in intact LNCaP cells overexpressing 17β-HSD3 (LNCaP[17β-HSD3]). Structural modifications of these two lead compounds could however be tested to produce a second generation of 17β-HSD3 inhibitors.